Development of an evidence-based clinical imaging diagnostic guideline for implant planning: Joint recommendations of the Korean Academy of Oral and Maxillofacial Radiology and National Evidence-based Healthcare Collaborating Agency - Kim, Min-Ji; Lee, Sam-Sun; Choi, Miyoung; Ha, Eun Ju; Lee, Chena; Kim, Jo-Eun; Heo, Min-Suk (Imaging science in dentistry, 2020)
This study was conducted to develop an evidence-based clinical imaging diagnostic guideline for implant planning, taking into account efficacy, benefits, and risks. The guideline development process employed the adaptation methodology used for Korean clinical imaging guidelines(K-CIG). Core databases(Ovid-Medline, Ovid-Embase, National Guideline Clearinghouse, Guideline International Network) and domestic databases (KoreaMed, KMbase, and KoMGI) were searched for guidelines. The retrieved articles were analyzed by 2 reviewers, and articles were selected using well-established inclusion criteria. The search identified 294 articles, of which 3 were selected as relevant guidelines. Based on those 3 guidelines, 3 recommendations for implant planning were derived. We recommend radiography or cone-beam computed tomography (CBCT) scanning for individual patients judged to require a cross-sectional image after reading of a panoramic X-ray image and a conventional intraoral radiological image. Various steps should be taken to raise awareness of these recommendations among clinicians and the public, and K-CIG should be regularly reviewed and revised.